Experimental study on erosion-corrosion behavior of liquid–solid swirling flow in pipeline. (February 2022) - Zhou, Hao; Ji, Qingfeng; Liu, Wen; Ma, Hongyan; Lei, Yun; Zhu, Keqian
Graphical abstract: Highlights: Velocity has the highest influence on the erosion-corrosion rate of swirling flow. The most influential interaction is the interaction of velocity and sand size. Swirling flow changes the sand distribution and promotes the mass transfer. The net effect of swirling flow on erosion-corrosion varies with sand size. Abstract: A multifactorial experimental research on erosion-corrosion behavior of liquid–solid swirling flow in pipeline was carried out by a circulating loop system in combination with a variety of test methods. The analysis of statistical significance reveals that the variation of erosion-corrosion rate is explained by three main effects (velocity, sand size, and sand concentration) and two interactions (velocity/sand size and sand size/sand concentration). An empirical linear regression equation with a R 2 value of 0.9043 was established to describe the correlation of erosion-corrosion rate with the test parameters and their interactions. It is concluded by microstructural examination of the working electrode surface that under the condition of liquid–solid swirling flow, cutting and corrosion pits are the primary forms of surface damage. The comparative analysis of erosion-corrosion between swirling flow and non-swirling flow shows that the net effect of swirling flow on erosion-corrosion varies with sand size. The corrosion product analysis by EDS and XPS show the presence of Fe2 O3 and CaCO3 under swirling flow and non-swirling flow conditions. Furthermore, the element content analysis of EDS and XPS showed that compared with the non-swirling flow, the oxygen content on the electrode surface under the swirling flow condition increased by 42.42% and 35.06%, respectively.